J Pediatr Clin Immunol 2020
DOI: 10.31546/jpci.1001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID19 on routine immunization: A cross-sectional study in Senegal

Abstract: The COVID 19 pandemic has prompted the world to implement drastic prevention methods based on limiting population movements that have an impact on public health policies such as vaccination. The objective of this work was to evaluate the impact of these prevention measures on routine vaccination in hospitals since the advent of the pandemic in Senegal. Methodology: This is a retrospective cross-sectional study carried out in August 2020 in the vaccination unit of the Abass NDAO hospital centre. We compared d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…8 Sow et al found that for the vaccines administered in the sixth week in April, the number of doses was 36 in 2018, 29 in 2019, and 15 in 2020, i.e., a 50% drop compared to March. 10 In July the number of doses administered was 40 in 2018, 35 in 2019, and 15 in 2020, a reduction of 42% compared to 2019. Countries could experience outbreaks of measles and other vaccine-preventable diseases if the uptake of routine vaccinations falls, undoing decades of progress.…”
Section: Discussionmentioning
confidence: 95%
“…8 Sow et al found that for the vaccines administered in the sixth week in April, the number of doses was 36 in 2018, 29 in 2019, and 15 in 2020, i.e., a 50% drop compared to March. 10 In July the number of doses administered was 40 in 2018, 35 in 2019, and 15 in 2020, a reduction of 42% compared to 2019. Countries could experience outbreaks of measles and other vaccine-preventable diseases if the uptake of routine vaccinations falls, undoing decades of progress.…”
Section: Discussionmentioning
confidence: 95%
“…[20] Studies have documented large decreases in immunization coverage in higher income countries during the early months of the pandemic, when countries had imposed social distancing and quarantine policies. [21][22][23][24][25] Much less is known about impacts in lower and middle income countries. Two largescale studies using the government's electronic immunization records in Pakistan found greater than 50% declines in daily vaccinations during the COVID-19 lockdown.…”
Section: Introductionmentioning
confidence: 99%
“…[26,27] A study using administrative records from one hospital in Senegal also documented decreases in vaccine doses given relative to previous year. [25] However, whether immunization coverage recovered after lockdowns were lifted and immunization activities resumed remains unclear.…”
Section: Introductionmentioning
confidence: 99%